Dielectric Relaxation Studies of 2-Butoxyethanol with Aniline and Substituted Anilines Using Time Domain Reflectometry. (18th February 2014) - Jeevanandham, P.; Kumar, S.; Periyasamy, P.; Kumbharkhane, A. C.
Abstract : The complex dielectric spectra of 2-butoxyethanol with aniline and substituted anilines like aniline, o -chloroaniline, m -chloroaniline, o -anisidine and m -anisidine binary mixtures in the composition of different volumes of percent (0%, 25%, 50%, 75%, and 100%) have been measured as a function of frequency between 10 MHz and 30 GHz at 298.15 K. The dielectric parameters like static dielectric constantε 0 and relaxation timeτ have been obtained by using least square fit method. By using these parametersε 0, τ, effective Kirkwood correlation factorg eff, corrective Kirkwood correlation factorg f, Bruggeman factorf B, excess dielectric constantε E, and excess inverse relaxation time1 / τ E values are calculated and discussed to yield information on the dipolar alignment and molecular rotation of the binary liquid mixtures. From all the derived dielectric parameters, molecular interactions are interpreted through hydrogen bonding.